Consolidating Wealth and Power - Tika Mardianti Lestari (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2026)
This study examines how the Basalamah family business was strengthened using political and social strategies. A qualitative method and case study approach was used for data collection, involving observation, in-depth interviews and documentation. Unlike previous business and political studies, this paper considers social capital as well as economic capital. This study complements political economy literature by demonstrating the influence of economic, political and religious identity forces on business and politics at the local level. The political strategy employed involved building a patronage network with local political elites, such as the Regent of Banyumas under the leadership of Joko Sudantoko, Aris Setiono and Mardjoko, and entering the world of practical politics by holding strategic positions in the Banyumas Regency Regional House of Representatives (Regency Council). Both strategies are important because informal connectivity is needed to build relationships with local political elites and to become directly involved in politics (i.e. policy-making) for the sake of business interests. The social strategy employed was to strengthen social networks and reinforce the religious social space through the Al-Irsyad Al-Islamiyyah social foundation in Purwokerto. This social strategy strengthens the bond between economic and political forces in perpetuating their business interests while safeguarding ethnic identity.